2010
DOI: 10.1542/peds.2009-2882
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Very Preterm Birth on Health Care Costs at Five Years of Age

Abstract: The health care costs during the fifth year of life in very preterm children with morbidities were 4.4-fold and in those without morbidities 1.4-fold compared with those of term control subjects. This emphasizes the importance of prevention of morbidities, especially CP, to reduce the long-term costs of prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 20 publications
3
48
0
1
Order By: Relevance
“…Research needs to begin at an early stage, particularly in light of the tremendous health care costs generated by the morbidities encountered when prenatal care is limited, and substance dependence is an issue (39,44). The need for gender related medical research is warranted, as sex-specific needs and problems can only be addressed through effective interventions when they have been determined by way of clinical research settings.…”
Section: Resultsmentioning
confidence: 99%
“…Research needs to begin at an early stage, particularly in light of the tremendous health care costs generated by the morbidities encountered when prenatal care is limited, and substance dependence is an issue (39,44). The need for gender related medical research is warranted, as sex-specific needs and problems can only be addressed through effective interventions when they have been determined by way of clinical research settings.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Preterm birth and its sequelae can have significant negative psychosocial and financial impacts on families of preterm newborns. [17][18][19][20] While the risks of mortality and morbidity affecting preterm newborns are considerably more frequent at lower gestational ages, 11 late preterm infants (sometimes called 'near-term') still experience significantly higher risks compared with babies born at term. 21 A systematic review of more than 29 million infants (mostly in high-income countries) found that, compared with term birth, late preterm birth was associated with increased 28-day mortality (Risk Ratio (RR) 5.9, 95% CI 5.0 to 6.9) and 1-year mortality (RR 3.7, 95% CI 2.9 to 4.6).…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Preterm-born infants, especially if born before 32 wk of gestation, incur substantially high costs for society (4,5). This is not only a major medical problem but a considerable trauma for affected families as well.…”
Section: Introductionmentioning
confidence: 99%
“…However, the causality of this association has not been confirmed. On the other hand, sugar-sweetened (SS) 4 beverages have been linked to obesity and to many adverse health outcomes (20,21). Both obesity (22) and high plasma glucose concentrations (23), even in nondiabetic subjects, are correlated with inflammatory response and preterm delivery.…”
Section: Introductionmentioning
confidence: 99%